Deep inelastic inclusive and diffractive scattering at Q2 values from 25 to 320 GeV2 with the ZEUS forward plug calorimeter - Chekanov, S; Derrick, M; Magill, S; Musgrave, B; Nicholass, D; Repond, J; Yoshida, R; Mattingly, M; Jechow, M; Pavel, N; Antonioli, P; Bari, G; et al. (2008)
Deep inelastic scattering and its diffractive component, e p → e′ γ* p → e′ X N, have been studied at HERA with the ZEUS detector using an integrated luminosity of 52.4 pb-1. The MX method has been used to extract the diffractive contribution. A wide range in the centre-of-mass energy W (37-245 GeV), photon virtuality Q2 (20-450 GeV2) and mass MX (0.28-35 GeV) is covered. The diffractive cross section for 2 < MX < 15 GeV rises strongly with W, the rise becoming steeper as Q2 increases. The data are also presented in terms of the diffractive structure function, F2D (3), of the proton. For fixed Q2 and fixed MX, xP F2D (3) shows a strong rise as xP → 0, where xP is the fraction of the proton momentum carried by the pomeron. For Bjorken-x < 1 × 10-3, xP F2D (3) shows positive log Q2 scaling violations, while for x ≥ 5 × 10-3 negative scaling violations are observed. The diffractive structure function is compatible with being leading twist. The data show that Regge factorisation is broken. © 2008 Elsevier B.V. All rights reserved.